2002
DOI: 10.1002/jcp.10127
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activity of Ca2+‐activated K+ channels by 1‐[2‐hydroxy‐3‐propyl‐4‐[(1H‐tetrazol‐5‐yl)butoxyl]phenyl] ethanone (LY‐171883) in neuroendocrine and neuroblastoma cell lines

Abstract: The effects of LY-171883, an orally active leukotriene antagonist, on membrane currents were examined in pituitary GH(3) and in neuroblastoma IMR-32 cells. In GH(3) cells, LY-171883 (1-300 microM) reversibly increased the amplitude of Ca(2+)-activated K(+) current in a concentration-dependent manner with an EC(50) value of 15 microM. In excised inside-out patches recorded from GH(3) cells, the application of LY-171883 into cytosolic face did not modify single channel conductance of large-conductance Ca(2+)-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Finding from the present results tends to be consistent with previous observations showing that different TZDs can regulate the activity of BK Ca channels (Wu et al, 2000; Li et al, 2002). Several studies have previously demonstrated that troglitazone and PIO might differentially perturb ionic currents in isolated cardiac myocytes and in pancreatic β cells (Ikeda and Watanabe, 1998; Sunaga et al, 1999).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Finding from the present results tends to be consistent with previous observations showing that different TZDs can regulate the activity of BK Ca channels (Wu et al, 2000; Li et al, 2002). Several studies have previously demonstrated that troglitazone and PIO might differentially perturb ionic currents in isolated cardiac myocytes and in pancreatic β cells (Ikeda and Watanabe, 1998; Sunaga et al, 1999).…”
Section: Discussionsupporting
confidence: 94%
“…They have been described to be functionally expressed in hippocampal neurons (Li et al, 2002; Huang et al, 2007; Wu et al, 2017). Another interesting paper has previously shown the function of Ca 2+ -activated K + channels in hippocampal pyramidal neurons (Storm, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an additional series of current‐clamp experiments were used to determine the effect of quercetin on changes in membrane potential of GH 3 cells. When the recording pipettes were filled with K + ‐containing solution, GH 3 cells, bathed in normal Tyrode's solution containing 1.8 mM CaCl 2 , had a resting membrane potential of −57 ± 6 mV (n = 18) under this current‐clamp condition (Li et al, 2002). The typical effect of quercetin on spontaneous action potentials is illustrated in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…The clonal rat pituitary GH 3 cells were obtained from the Culture Collection and Research Center (CCRC‐60015; Hsinchu, Taiwan). Cells were cultured in 50‐ml Ham's F‐12 medium (Life Technologies, Grand Island, NY) that was supplemented with 15% horse serum (v/v), 2.5% fetal calf serum (v/v), and 2 mM l ‐glutamate (Life Technologies) in a 5% carbon dioxide atmosphere at 37°C (Wu et al, 1998; Li et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…(6)), chlorzoxazone [107] (Fig. (6)) and LY-1783 [108], which have been reported to possess BK-opener properties, even multiply such a chemical complexity. Ample chemical diversity is reflected in the miscellaneous pharmacological effects on BK channels and may underlie the action at different receptors in the channels and/or interaction at the same receptor but with a different set of amino acids.…”
Section: Structure Activity Relationshipsmentioning
confidence: 98%